An improved internal and external resilience framework for new high school teachers - Mat Yamin, Wan Mohd Agil; Hooi Lian, Lim (International Journal of Evaluation and Research in Education (IJERE), 2025)
The concept of resilience gained widespread recognition in the teaching profession as some new high school teachers are confronted with various challenges and pressures, which cause some of them to leave the profession during the first four to five years of their employment. By considering the guidance new high school teachers need to survive and retain their profession, this qualitative study aimed to identify resilient strategies used by new high school teachers. This study focuses on semi-structured interviews with twelve new high school teachers. After performing a thematic analysis, this study found internal and external resilience, with five strategies new high school teachers use to overcome challenges and pressures (internal: professional, emotional, and motivational; external: social and spiritual). This study validates the applicability of Mansfield’s four-dimensional teacher resilience frameworks (professional, emotional, motivational, and social resilience) to the resistance of new high school teachers in Malaysia. This study also improved Mansfield’s framework through its findings by considering a new dimension, spiritual resilience. The Malaysian Ministry of Education, specifically through public universities that train future high school teachers, can use these resilient strategies to develop intervention programs that enhance their resilience, thereby fulfilling the objectives of the Malaysia Education Development Plan (MEDP) 2013–2025.